The origins of John's gospel - Porter, Stanley E., 1956- (Johannine Studies, 2015)
The essays in The Origins of John's Gospel , gathered by Stanley E. Porter and Hughson T. Ong, either survey or discuss in detail various areas and topics in Johannine scholarship, especially in the study of John's Gospel. These include the authorship and dating, sources, and traditions of John's Gospel, its structure and composition, the Johannine community, and Johannine anti-Judaism and the Son of Man sayings. Collectively, these essays offer important contributions to various areas and topics of research relating to the origins of John's Gospel.